The Impact of the 5E Learning Cycle Model Based on the STEM Approach on Scientific Attitudes and Science Learning Outcomes - Wiriani, Ni Made Adi; Ardana, I Made (Universitas Pendidikan Ganesha, 2022)
It was found that students' learning outcomes and scientific attitudes were low. This study aims to analyze Cycle 5E based on the STEM approach to scientific attitudes and science learning outcomes. This research is experimental. The population is 294 students. Methods of collecting data are test and non-test. The instruments used are questionnaire sheets or questionnaires for scientific attitudes and science learning outcomes tests. The technique of analyzing the data is descriptive analysis and inferential statistics. The results of the research are that there are differences in scientific attitudes between students who take part in learning using the 5E Learning Cycle based on the STEM approach and students who use the direct learning model, with a significant level of 0.026. There are differences in science learning outcomes between students who take lessons using Learning Cycle 5E based on the STEM approach and students who use direct learning models, with a significance level of less than 0.000. It was concluded that there were differences in scientific attitudes and science learning outcomes between students who participated in learning using Learning Cycle 5E based on the STEM approach and students who participated in direct learning. This research implies that the 5E learning cycle based on the STEM approach can improve scientific attitudes and science learning outcomes.